Estudo ecotoxicológico em machos e fêmeas de Poecilia reticulata expostos a um efluente pesqueiro do município de Goiânia (GO) - Machado, Rafael Cosme (2015)
The toxicity of environmental contaminants such as polycyclic aromatic hydrocarbons (PAHs), heavy metals and cyanotoxins has frequently been investigated for its biochemical, cellular and pathological aspects on animals and humans. Among heavy metals, copper is a chemical element that in trace concentrations is commonly found in natural and artificial lakes. The increase in the concentration of this metal in fishing ponds due to the use of algicides, such as CuSO4, or by leaching of the soil, is responsible for the intoxication of aquatic organisms, particularly fish, therefore representing a potential risk to human health. The aim of this study was to determine the phytoplanktonic composition, physicochemical characteristics and the main organic and inorganic contaminants of the water bodies, as well as to evaluate the acute toxicity of the crude effluent from the Jaó fishing pond using histological, ethological, genotoxic and enzymatic endpoints in Poecilia reticulata. Concentrations of Cu2+, phosphorus and nitrogen were higher than allowed by CONAMA resolutions 357 and 430, which, in synergy with other chemical contaminants in the mixture, caused acute toxicity to P. reticulata exposed during the dry season (EC50-96h of 60.48% for males and 85.08% for females) and for rainy (EC50-96h of 32.29% for males and of 49.50% for females). This study demonstrated that copper has a pronounced deposition on the hepatic parenchyma of males and females of P. reticulata. In the analysis of the medial portion of the small intestine, it was observed that the increase in mucin production is a physiological response to stress induced by copper, quantified in the fishing effluent, so that the same results were observed when the specimens were exposed to the average lethal concentration of 96 hours (CL50-96h) to Cu2+ (0.82 ± 0.17 mg.L-1 of CuSO4). It was also observed the genotoxic effect of the effluent from the dry and rainy season on the P. reticulata erythrocytes, so that the females had a higher sensitivity (p <0.05) to the copper contamination. In enzymatic assays, the activity of carboxylesterase (CarbE) was reduced (p <0.05) in females exposed to the rainy season effluent and no changes in the activity of catalase (CAT) and glutathione-S-transferase (GST) were observed. Mitigating measures should be taken to reduce contamination by copper and macronutrients in the fishing pond studied, thus avoiding potential risks to the aquatic and human communities.